Proselytization revisited rights talk, free markets and culture wars - Hackett, Rosalind I. J. (London ; Oakville, CT : Equinox Pub., 2008)
The current volume updates and expands earlier studies of proselytism, and explores more thoroughly the theoretical and practical implications of proselytization and anti-proselytization, notably within the current phase of democratization and globalization. Several authors offer analyses of the new actors, movements, and territories now associated with proselytic activity, demonstrating its global significance.
Revisiting proselytization in the context of rights talk, free markets and culture wars / Rosalind I. Hackett -- Conflicts over proselytization -- an overview and comparative perspective / Jean-Francois Mayer -- Conversion of the world: Proselytization in India and the universalization of Christianity / Jacob De Roover and Sarah Claerhout -- The logic of anti-proselytization, revisited / Grace Kao -- The changing face of Christian proselytization: New actors from the global South / Paul Freston -- Muslim Apostasy, Christian conversion, and religious freedom in Egypt / Heather J. Sharkey -- Seeing is more than believing: Posters and proselytization in Nigeria / F.-K. Asonzeh Ukah -- Buddhism and the politics of conversion in Sri Lanka / Steve C. Berkwitz -- Merit and the search for inner peace: the discourses and technology of Dhammakaya proselytization / Rachelle M. Scott -- Asia's Antioch: Evangelical Christianity and proselytism in Singapore / Jean DeBernardi -- False consciousness and the jargon of Authenticity: Religion and nationalism in the Christianised Lowland Philippines / Paul-Francois Tremlett -- Salvation through secular protest: the development of Falun Gong proselytization / Patsy Rahn -- The social and legal context of proselytization in contemporary Japanese religions / Mark Mullins -- Negotiating proselytism in 21st century Russia / Olga Kazmina -- Between Da'wa and mission: Turkish Islamic movements in the Turkic world (Central Asia and the Caucasus) / Bayram Balci -- Spiritual Wars in the 10-40 window: Korean proselytism among Russia's Asian minorities / Julia S. Kovalchuk -- Proselytization or information? Wicca and the internet / Shawn Arthur -- You can't talk to an empty stomach: Faith-based activism, Holistic Evangelism, and the publicity of Evangelical engagement / Ormri Elisha -- Proselytization: Closing thoughts from a sociologist / James T. Richardson.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Proselytizing; Religion; Proselytizing; RELIGION / Education; Electronic books